1980
DOI: 10.1177/002224298004400210
|View full text |Cite
|
Sign up to set email alerts
|

Fishbein's Intentions Model: A Test of External and Pragmatic Validity

Abstract: An unobtrusive measure of overt behavior and personal verbal responses is employed to examine the external validity of the Extended or Intentions Model. An application is tested involving the model's usefulness in formulating promotional strategies designed to increase the number of loan applications at a credit union.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
1

Year Published

1982
1982
2007
2007

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(21 citation statements)
references
References 26 publications
2
18
1
Order By: Relevance
“…Moreover, the attitudinai component alone was inadequate to predict intent; the normative and affective components were also required. This finding replicated those in [3], [18], [20] in other decision domains. Taken together, the research significantly questions the adequacy of traditional decision-theoretic models incorporately an exclusively atti tudinai component.…”
Section: One Possible Explanation For the Lack Of Prediction Of The Tsupporting
confidence: 83%
See 3 more Smart Citations
“…Moreover, the attitudinai component alone was inadequate to predict intent; the normative and affective components were also required. This finding replicated those in [3], [18], [20] in other decision domains. Taken together, the research significantly questions the adequacy of traditional decision-theoretic models incorporately an exclusively atti tudinai component.…”
Section: One Possible Explanation For the Lack Of Prediction Of The Tsupporting
confidence: 83%
“…Bagozzi [3] and Ryan and Bonfield [20] also found that a general affective component was significantly related to people's decisions. Other authors also have discussed the importance of an affective component in choice behavior.…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…Therefore, the theory has been applied across a variety of domains, and there is ample evidence that it is very useful in predicting consumer behavior through utilizing attitudes and behavioral intentions as a mediator (Ryan & Bonfield, 1980). It also provides a relatively simple framework for identifying where and how to target consumers' behavioral change attempts (Sheppard, Hartwick, & Warshaw, 1988).…”
Section: Theoretical Backgroundmentioning
confidence: 99%